P.093 Visual outcomes after expanded endoscopic endonasal resection of suprasellar meningiomas and optic nerve decompression. (5th June 2019) - Yang, K; Ellenbogen, Y; Kim, J; Rodriguez, A; Sommer, D; Reddy, K
Abstract : Background: The Endoscopic endonasal approach (EEA) has become increasingly popular in the treatment of suprasellar meningiomas, which often cause visual symptoms due to compression of the anterior optic apparatus.Methods: We performed a retrospective chart review on patients who underwent EEA optic nerve decompression and resection of suprasellar meningiomas between January 1 st 2005 and December 1 st 2018 at McMaster University.Results: The mean age of our patients was 59.8 years. We treated 9 male and 23 female patients, with a mean follow up of 6.29 years. 23 patients (71.9%) presented with visual symptoms, with a mean duration of 8.65 months. In our patient cohort, 95.5% had stable or improved visual acuity postoperatively. Less than six months of visual decline was more likely to be associated with postoperative improvement of visual acuity, with an odds ratio (OR) of 0.0222 (95% CI: 0.0017–0.289, p<0.05); as well as visual field (OR:0.0625; 95% CI, 0.0042–0.915, p<0.05). Additionally, the absence of RAPD was associated with improved postoperative visual acuity (OR: 0.0675; 95% CI, 0.0354–0.706, p<0.05).Conclusions: Endoscopic endonasal approach can achieve good visual outcome in patients harboring suprasellar meningiomas. Symptom duration of less than six months and absence of RAPD were positive predictor of postoperative visual outcome.